Topical issues in global value chains research - Damijan, Jože (Teorija in praksa, 2015)
The dynamics of the global economy and international trade are increasingly characterised by global value chains (GVCs), within which intermediate goods and services are traded in fragmented and internationally dispersed production processes. Successful integration of firms and countries in GVCs is increasingly important for their development and integration in the international economy. Based on an analysis of conceptual, empirical an policy-related literature on (i) GVCs in development economics and international trade models, (ii) factors behind the proliferation of GVCs, (iii) development effects, benefits and risks of integrating into GVCs, (iv) importance of GVCs for international trade, (v) theoretical considerations and empirical evidence on firms' (MNEs%) decision-making related to the establishing and modality of GVCs, (vi) GVC governance and upgrading a firm%s position within a GVC, and (vii) GVC-related changes to economic policy, we identify the priority topics for future GVCs research that are the most important for the economies of catching-up countries ("factory economies") and their firms.
Keywords: direct investments; direktne investicije; integracija; integration; international trade; mednarodna menjava; mednarodna trgovina; preskrbovalne verige; supply chain